Measurement of coronary artery calcium volume using ultra-high-resolution computed tomography: A preliminary phantom and cadaver study. (2020) - Fukumoto, Wataru; Nagaoka, Mami; Higaki, Toru; Tatsugami, Fuminari; Nakamura, Yuko; Oostveen, Luuk; Klein, Willemijn; Prokop, Mathias; Awai, Kazuo
Highlights: Small calcifications were moe accurately detectable on SHR- than NR images. The mean CAC volume was significantly higher on SHR- than NR images of the cadavers. SHR imaging may facilitate the accurate quantification of the CAC. Abstract: Objectives: In this phantom- and cadaver study we investigated the differences of coronary artery calcium (CAC) volume on ultra-high-resolution computed tomography (U-HRCT) scans and conventional CT. Methods: We scanned a coronary calcium phantom and the coronary arteries of five cadavers using U-HRCT in normal- and super-high resolution (NR, SHR) mode. The NR mode was similar to conventional CT; 896 detector channels, a matrix size of 512, and a slice thickness of 0.5 mm were applied. In SHR mode, we used 1792 detector channels, a matrix size of 1024, and a slice thickness of 0.25 mm. The CAC volume on NR- and SHR images were recorded. Differences in the physical- and the calculated CAC volume were defined as the error value and compared between NR- and SHR images of the phantom. Differences between the CAC volume on NR- and SHR scans of the cadavers were also recorded. Results: The mean error value was lower on SHR- than NR images of the phantom (14.0 %, SD 11.1 vs 20.1 %, SD 15.2, p = 0.01). The mean CAC volume was significantly higher on SHR- than NR images of the cadavers (153.4 mm 3, SD 161.0 vs 144.7 mm 3, SD 164.8, p < 0.01). Conclusions: As small calcifications were more clearly visualized on U-HRCT images in SHR mode than on conventional (NR) CT scans, SHR imaging may facilitate the accurate quantification of the CAC.